Potential regulatory obstacles to cross-border and acquisitions in the EU banking sector - Anna Garella; Massimiliano Rimarchi; Davide Stroppa (European Banking Authority (EBA), 2020)
Over the past decade, cross-border merger and acquisition (M&A) activity in the EU banking sector has remained far below its pre-crisis levels, despite the regulatory reforms implemented after the financial crisis. While the EU equipped itself with the Single Rulebook, convergent supervisory practices, a common crisis management framework and the creation of the Banking Union, ring-fencing and limits to the circulation of funds across borders are still present and the EU still does not reap the full benefits of the Single Market. The purpose of this paper is to map and analyse the elements of the current EU prudential framework that create obstacles to banking groups operating across borders. The results highlight the existence of a number of potential issues at both regulatory and supervisory levels. First, policy reviews, cases and survey-based evidence suggest that the current regulatory framework relies on a territorial approach (cross-border waivers for capital and minimum requirements for own funds and eligible liabilities (MREL), inefficient intra-group financial support arrangements, a multiplicity of macroprudential tools and the existence of options and national discretions within the Single Rulebook), favours pre-positioning resources with the subsidiaries and entails market fragmentation. Ultimately, this may endanger the comparability of institutions across countries and reduce the incentive to conduct cross-border consolidation. Second, despite the progress made in achieving convergence of supervisory practices across the EU, a number of approaches are not yet fully consistent, in particular with respect to the link between prudential requirements and restrictions on distributions, and to a more transparent approach when setting risk-by-risk requirements. The absence of common and fully transparent EU practices for prudential assessment of M&A transactions, including the determination of capital requirements, further adds to the complexity. Finally, it is also suggested that the completion of the Banking Union, by further strengthening the institutional cooperation among Member States and national authorities, has a fundamental role to play in freeing up the potential of enhanced financial integration. There should also be no further delay in the progress made towards the Banking Union's achievement of single jurisdiction status.
Keywords: 330; M&A; prudential regulation; prudential waivers; Banking Union; MREL; qualifying holdings